Serum concentrations of endothelial cell adhesion molecules and their shedding enzymes and early onset sepsis in newborns in Suriname - Rens Zonneveld; Rianne M Jongman; Amadu Juliana; Grietje Molema; Matijs van Meurs; Frans B Plötz (BMJ Publishing Group, 2018)
Background Early onset sepsis (EOS) is defined as onset of sepsis within 72 hours after birth. Leucocyte-endothelial interactions play a pivotal part in EOS pathophysiology. Endothelial cell adhesion molecules (CAMs) orchestrate these interactions and their soluble isoforms (sCAMs) are released into the vasculature by enzymes called sheddases.Purpose This study was undertaken to explore further the pathophysiology of EOS and to investigate the potential of sCAM and their sheddases as potential biomarkers for EOS.Methods Stored serum aliquots were used from 71 Surinamese newborns suspected of EOS and 20 healthy newborns from an earlier study. Serum had been collected within 72 hours after birth and six (8.6%) newborns had a positive blood culture with gram-negative pathogens. Concentrations of sCAMs sP-selectin, sE-selectin, soluble vascular cell adhesion molecule-1 , intercellular adhesion molecule-1 and platelet and endothelial cell adhesion molecule-1, sheddases matrix metalloproteinase-9 (MMP-9) and neutrophil elastase (NE) and sheddase antagonist tissue-inhibitor of metalloproteinases-1 (TIMP-1) were measured simultaneously with Luminex and ELISA.Results MMP-9 and TIMP-1 levels were measured in serum of n=91 newborns and sCAMs and NE levels in serum of n=80 newborns, respectively. We found no differences in median concentrations of sCAMs, MMP-9 and TIMP-1 or NE between blood culture positive EOS, blood culture negative EOS and control groups at start of antibiotic treatment.Conclusions Our data indicate that serum concentrations of sCAMs and their sheddases have no clinical utility as biomarkers for EOS.Trial registration number NCT02486783. Results